2012
DOI: 10.1063/1.4773460
|View full text |Cite
|
Sign up to set email alerts
|

Angle-resolved photoemission studies of the superconducting gap symmetry in Fe-based superconductors

Abstract: The superconducting gap is the fundamental parameter that characterizes the superconducting state, and its symmetry is a direct consequence of the mechanism responsible for Cooper pairing. Here we discuss about angle-resolved photoemission spectroscopy measurements of the superconducting gap in the Fe-based high-temperature superconductors. We show that the superconducting gap is Fermi surface dependent and nodeless with small anisotropy, or more precisely, a function of the momentum location in the Brillouin … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…As shown in Ref. [5], this result is also perfectly consistent with STM data on the same material [151]. The gap shape can clearly be fitted by a ∆0 + ∆1 cos[4(θ + φ)] function.…”
Section: Nodes and Superconducting Gap Anisotropysupporting
confidence: 90%
“…As shown in Ref. [5], this result is also perfectly consistent with STM data on the same material [151]. The gap shape can clearly be fitted by a ∆0 + ∆1 cos[4(θ + φ)] function.…”
Section: Nodes and Superconducting Gap Anisotropysupporting
confidence: 90%
“…The fit of the experimental data to a global gap function derived from short-range interactions by using a single parameter for all the FS sheets pushes towards a local pairing origin in this particular material, similar to the other Fe-based superconductors. [20] The fit is not perfect, suggesting that some parameters have been ignored. For instance, as mentioned above, there must be a finite interlayer interaction responsible for the modulation of the SC gap on the 𝛼 FS shown in Fig.…”
Section: (Received 28 March 2014)mentioning
confidence: 99%
“…However, in general, this state should have nodes on the electron pockets if the sign change between them exists or shows large anisotropicity of the SC gaps. Although a non-negligible anisotropicity of the SC gap was observed by ARPES in LiFeAs [25,26], the anisotropicities in most Fe-based superconductors are small [29]. Most recently, it was also suggested that an odd-parity SC pairing term [30] can produce the exact anti-phase s ± state [31,32].…”
mentioning
confidence: 99%